Program Edukasi Kesehatan Mental untuk Mahasiswa Informatika sebagai Upaya Pencegahan Stres Akademik dan Karier - Gutara, Mohamad Yudha; Hesta, Ogy Yan; Rizanty, Rahmadhania (Universitas Pahlawan Tuanku Tambusai, 2026)
Informatics students often experience academic stress and career anxiety due to heavy coursework demands, the pressure to master technical skills, and competition in the technology job market. To address these challenges, a community service program titled “Self Development with HIMATI: Mental Health for Student and Aspiring IT Professional” was held on October 27, 2024, at the STT NF Campus B Auditorium, involving approximately 80 participants. Through an interactive seminar, students received education on mental health, emotional regulation strategies, academic stress management, and career readiness. Evaluation results showed increased understanding, active participation, and improved readiness to apply stress-management strategies in daily academic activities. This program demonstrates that mental health education delivered through interactive seminars can serve as an effective preventive effort to support psychological well-being and self-development among informatics students.